Osteomyelitis with abscess associated with acute closed upper humerus fracture in an adult: A case report - John G. Skedros; Tyler R. Smith; John T. Cronin (Clinical Case Reports, 2023)
Key Clinical Message A 64‐year‐old female presented with malaise and fever 11 days after a closed, minimally displaced humerus surgical neck fracture. MR imaging revealed an abscess around the fracture, which is a very rare occurrence in adults. Two open debridements and IV antibiotics eradicated the infection. Reverse total shoulder arthroplasty was eventually performed for fracture nonunion.